Valency based topological descriptors of para line graph of Remdesivir used in the prevention of Corona virus. Issue 4 (19th May 2022) - Rosary, Maria Singaraj; Haoer, Raad Sehen; Cancan, Murat; Tas, Ziyattin
Abstract: Molecular descriptors explore the properties of graphs that endure constant after recurrent changing in graph. These indices aid us to forecast chemical combinations like entropy, enthalpy formation, area of surfaces and formation of heat. In structural chemistry para-line graphs are very popular. In this article, we present some valency based topological indices for the para line graph of Remdesivir.